(-)-Epigallocatechin-3-gallate and hydroxytyrosol improved antioxidative and anti-inflammatory responses in bovine mammary epithelial cells. (11th June 2019) - Basiricò, L.; Morera, P.; Dipasquale, D.; Bernini, R.; Santi, L.; Romani, A.; Lacetera, N.; Bernabucci, U.
Abstract : (-)-Epigallocatechin-3-gallate (EGCG ), the major phenolic compound of green tea, and hydroxytyrosol (HTyr ), a phenol found in olive oil, have received attention due to their wide-ranging health benefits. To date, there are no studies that report their effect in bovine mammary gland. Therefore, the aim of this study was to evaluate the anti-oxidative and anti-inflammatory effects of EGCG and HTyr in bovine mammary epithelial cell line (BME-UV1 ) and to compare their antioxidant and anti-inflammatory in vitro efficacy. Sample of EGCG was obtained from a commercially available green tea extract while pure HTyr was synthetized in our laboratories. The mammary oxidative stress and inflammatory responses were assessed by measuring the oxidative stress biomarkers and the gene expression of inflammatory cytokines. To evaluate the cellular antioxidant response, glutathione (GSH /GSSH ), γ-glutamylcysteine ligase activity, reactive oxygen species and malondialdehyde (MDA ) production were measured after 48-h incubation of 50 µM EGCG or 50 µM of HTyr. Reactive oxygen species production after 3 h of hydrogen peroxide (50 µM H2 O2 ) or lipopolysaccharide (20 µM LPS ) exposure was quantified to evaluate and to compare the potential protection of EGCG and HTyr against H2 O2 -induced oxidative stress and LPS-induced inflammation. The anti-inflammatory activity of EGCG and HTyr was investigated by the evaluation of pro and anti-inflammatory interleukins (tumor necrosis factor (TNF )-α, interleukin (IL)-1β, IL-6 and IL-10 ) messenger RNA abundance after treatment of cells for 3 h with 20 µM of LPS. Data were analyzed by one-way ANOVA. (-)-Epigallocatechin-3-gallate or HTyr treatments induced higher concentrations of intracellular GSH compared to control cells, matched by an increase of γ-glutamylcysteine ligase activity mainly in cells treated with HTyr. Interestingly, EGCG and HTyr prevented oxidative lipid damage in the BME-UV1 cells by a reduction of intracellular MDA levels. (-)-Epigallocatechin-3-gallate and HTyr were able to enhance cell resistance against H2 O2 -induced oxidative stress. It was found that EGCG and HTyr elicited a reduction of the three inflammatory cytokines TNF-α, IL-1β, IL-6 and an increase of the anti-inflammatory cytokine IL-10. Hydroxytyrosol has proved to be a strong antioxidant compound, and EGCG has shown mainly an anti-inflammatory profile. These results indicated that EGCG and HTyr may provide dual protection because they were able to attenuate oxidative stress and inflammatory responses, suggesting that these phenolic compounds are potential natural alternatives to be used in dairy cattle as feed supplement for reducing the development of oxidative and inflammatory processes related to parturition or as topical treatments for the control of bovine intramammary inflammation.